Risk of Anaemia in Population of Healthy Young People Inhabiting a Region in Central Europe - Małgorzata Szczuko; Izabela Gutowska; Teresa Seidler; Mariusz Mierzwa; Ewa Stachowska; Dariusz Chlubek (Journal of Nutrition and Metabolism)
It is quite unbelievable but significant percentage of young healthy women is at risk of anaemia despite proper nutritional state. In this study we decided to determine the lack or excess of which nutrients in a diet can lead to any effects. The major cause of anaemia is not, as in many studies on nutritional status, the deficiency in iron in a diet. Iron intake in women with anaemia exceeded AI (Adequate Intake) level. 120 people took part in the study. Average HGB concentration in female group amounted to 12.45 g/dL and in male group to 14.35 g/dL. Anaemia was determined in 29% women and 4.2% men. In group of women with anaemia a statistically higher intake of SFA, cholesterol, and sucrose and lower intake of pyridoxine, folacin, niacin, and vitamin E, Mn, Cu, Zn, Fe, and Mg were determined. In a group of men with low haemoglobin concentration a statistically higher intake of sucrose but lower intake of fat, especially SFA and MUFA, vitamin C and zinc were observed. Therefore, together with anaemia in the group of women there are coexisting deficiencies in other nutrients, as compared to the group of men. Prevention in both groups should include various supplements.